Management Strategy: Business Challenges and Working Ethos in the Era of Covid-19 Pandemic - Jim Hoy Yam; Widarto Rachbini (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
The Covid-19 pandemic has shaken the business world which has brought down many retail businesses which indirectly impacted manufacturing companies. The retailers have done changes in serving customers; the phenomenon has shifted consumer behavior from the classic face-to-face way of purchasing to online purchases. Then has created new challenges in the business world and has an impact on business operations at large. The purposes of this research are to generate some fresh ideas to support the working ethos in the era of the Covid-19 Pandemic. The method used in research is a literature review, which describes the findings that new business situations have to be tamed by entrepreneurs and are unavoidable. The solution is an idea to set a custom work ethic; in terms of improving work ethic to proactive action, which includes several particular attitudes such as smart, respectful, honest, and assertive. Expectedly the work ethic will motivate creative strategies to overcome the business challenges of a new phenomenon. In the end, consistent implementation of work ethic is a must to support business survival.